2002
DOI: 10.11150/kansenshogakuzasshi1970.76.721
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and the Valuation of eaeA Gene of Enteropathogenic Escherichia coli (EPEC) or aggR Gene of Enteroaggregative E. coli (EAggEC) in the Strains Isolated from Patients in Sporadic Diarrhea Cases

Abstract: To clarify the pathogenic role of enteropathogenic Escherichia coli (EPEC) or enteroaggregative E. coli (EAggEC), the possession of eaeA gene of EPEC or aggR gene of EAggEC in the strains isolated from 525 patients in sporadic diarrhea cases during 3 years (1998-2000) in Tama, Tokyo was investigated by a PCR method. The eaeA-positive E. coli strains were confirmed from 23 cases including 5 cases detected verotoxin-producing E. coli (VTEC), and those except VTEC strains (18 cases, 3.4%) were the 5th predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This is similar to previously reported observations [ 4 ]. In human disease, EPEC is known to cause acute, watery diarrhea but not hematochezia, especially in infants [ 8 , 14 ]. In our study, hematochezia caused by desquamation of cecal epithelial cells was observed in animals as a main symptom, but differed from that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to previously reported observations [ 4 ]. In human disease, EPEC is known to cause acute, watery diarrhea but not hematochezia, especially in infants [ 8 , 14 ]. In our study, hematochezia caused by desquamation of cecal epithelial cells was observed in animals as a main symptom, but differed from that in humans.…”
Section: Discussionmentioning
confidence: 99%